2021
DOI: 10.1093/qjmed/hcab245
|View full text |Cite
|
Sign up to set email alerts
|

Non-episodic angioedema with eosinophilia after BNT162b2 mRNA COVID-19 vaccination

Abstract: A 77-year-old Japanese woman presented with peripheral oedema following COVID-19 vaccination. Three weeks before, the day after the second dose of BNT162b2 mRNA COVID-19 vaccination, she presented with low-grade fever, peripheral oedema and arthralgia of the bilateral foot joint. Fever and arthralgia were relieved spontaneously within a week. Since there was no improvement in the peripheral oedema, she was referred to our department. Her medical history revealed type 2 diabetes mellitus and dyslipidaemia, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“… 18 Reports of adverse reactions from COVID-19 vaccines are increasing. In some studies, eosinophilia or eosinophilic reactions were reported, 19 20 21 but some of them were from other forms of the vaccine, not the mRNA vaccine, 22 23 and there were no cases of eosinophilic gastroenteritis. The relationship between COVID-19 vaccines and EGE is not yet clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Reports of adverse reactions from COVID-19 vaccines are increasing. In some studies, eosinophilia or eosinophilic reactions were reported, 19 20 21 but some of them were from other forms of the vaccine, not the mRNA vaccine, 22 23 and there were no cases of eosinophilic gastroenteritis. The relationship between COVID-19 vaccines and EGE is not yet clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of NEAE is unknown, the fact that it is more common among women and occurs after infection or drug exposure suggests that NEAE is the result of an abnormal immune response to various exogenous stimuli in genetically susceptible individuals, with sex hormones likely playing a role [ 3 ] . Eosinophilic disease after COVID-19 infection has been reported, namely eosinophilic pneumonia and eosinophilic granulomatosis with polyangiitis [ 4 , 5 ] . In addition, there have been reports of NEAE after vaccination against SARS-CoV-2 [ 6 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Alopecia areata (AA) [74], bullous pemphigoid [75], COVID arm (local injection site reaction) [76,77], eosinophilic cellulitis (Wells syndrome) [22], eosinophilic panniculitis [24], erythema multiforme [78], herpes zoster (skin, oral and facial palsy) [53,57,79,80], leukocytoclastic vasculitis [81], non-episodic angioedema with eosinophilia [23], psoriasis [82], Stevens-Johnson syndrome [83], subacute cutaneous lupus erythematosus [11,84,85], and urticaria [77] have been reported following COVID-19 vaccination (Table 1). AA is an autoimmune disease, and an increase in IFN-γ and inflammatory cytokines, including IL-6 and IL-1β, have been reported [86].…”
Section: Skin Diseasesmentioning
confidence: 99%
“…Eosinophilia may also be responsible for post-vaccine adverse reactions. Eosinophilic myocarditis, eosinophilic pneumonia, EGPA (relapse), eosinophilic cellulitis, eosinophilic panniculitis, and non-episodic angioedema with eosinophilia have been reported following COVID-19 vaccination [20][21][22][23][24][25]. SARS-CoV-1 vaccines have also been shown to induce eosinophilia in the lungs of mice [114].…”
Section: Eosinophiliamentioning
confidence: 99%
See 1 more Smart Citation